PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO(DER), RETURN ON ASSET(ROA) TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR SUB SEKTOR TRANSPORTASI DI BURSA EFEK INDONESIA TAHUN 2015-2018 - Rahmat Prasetyo Mulyono, Elfreda Aplonia Lau dan Umi Kulsum (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2021)
This study aims to determine and analyze the effect partially and simultaneously of the Current Ratio (CR) Debt to Equity Ratio (DER), Return On Asset (ROA) on the stock prices of Transportation Sub-Sector companies listed on the Indonesia Stock Exchange 2015-2018. .The theoretical basis of this research is financial management which focuses on each ratio measured by Current Ratio (CR), Debt To Equity Ratio (DER), Return On Asset (ROA).The analysis tool used is Multiple Linear Regression. The data used are financial statement data from 2015 to 2018 in the Transportation Sub-Sector companies listed on the Indonesia Stock Exchange.The results show that the Current Ratio has a positive and insignificant effect on the stock prices of the Transportation Sub-Sector in 2015-2018. Debt Equity Ratio has a negative and insignificant effect on the Stock Price of the Transportation Sub-Sector in 2015-2018, Return On Assets has a significant positive effect on the Share Price of the Transportation Sub-Sector in 2015-2018. Current Ratio (CR), Debt To Equity Ratio (DER), Return On Asset (ROA) simultaneously affect stock prices.